The Presence and Image of the Translator in Narrative Discourse: towards a Definition of the Translator's Ethos - Spoturno, Maria Laura (2017)
This paper aims at exploring the configuration of the discursive image or ethos attached to the enunciative subject assuming the responsibility for the enunciation of translated narrative (Ducrot 1984; Amossy 1999, 2009, 2012). Our concern will be the study of the modeling of ethos affecting the Translator, understood here not as an empirical subject but as a discursive one. Accordingly, the purpose of this paper is two-fold. On a theoretical and methodological level, this paper intends to elaborate the category of Translator's ethos by articulating contributions from two distinct but related areas, translation studies (Schiavi 1996; Hermans 2010 [1996]) and discourse studies (Ducrot 1984; Amossy 1999, 2009, 2012), in an attempt to further explore an already posed question in the field of translation studies: "Exactly whose voice comes to us when we read translated discourse?" (Hermans 2010 [1996]: 197). On the analytical level, this interdisciplinary approach will be exemplified by the analysis of Chicana novel Caramelo or Puro Cuento by Sandra Cisneros (2002a) and its corresponding translation into Spanish carried out by Liliana Valenzuela (Cisneros 2002b). In examining the construction of ethos, our approach will combine textual, contextual and paratextual analyses of the texts.